The Ghrelin-AgRP Neuron Nexus in Anorexia Nervosa: Implications for Metabolic and Behavioral Adaptations - Méquinion, Mathieu; Foldi, Claire J.; Andrews, Zane B. (Frontiers in Nutrition, 2020)
Anorexia Nervosa (AN) is viewed as primarily a psychiatric disorder owing to the considerable behavioural and genetic overlap with mood disorders and other psychiatric traits. However, the recent reconceptualization of AN as one of both psychiatric and metabolic aetiology suggests that metabolic circuits conveying hunger or sensitive to signals of hunger may be a critical nexus linking metabolic dysfunction to mood disturbances. Within the brain, hunger is primarily percieved by Agouti-related (AgRP) neurons and hunger increases plasma concentrations of the hormone ghrelin, which targets ghrelin receptors on AgRP neurons to facilitate metabolic adaptations to low energy availability. However, beyond the fundamental role in maintaining hunger signalling, AgRP neurons regulate a diverse range of behaviours such as motivation, locomotor activity, negative reinforcement, anxiety and obsession and a key factor involved in the manifestation of these behavioural changes in response to activation is the presence or absence of food availability. These changes can be considered adaptive in that they promote affective food-seeking strategies in environments with limited food availability. However, it also suggests that these neurons, so well-studied for their metabolic control, shape mood-related behaviours in a context-dependent manner and dysfunctional control leads not only to metabolic problems but also potentially mood-related problems. The aim of this review is to underline the potential role of AgRP neurons and ghrelin signalling in both the metabolic and behavioural changes observed in anorexia nervosa. We aim to highlight the most recent studies on AgRP neurons and ghrelin signalling and integrate their metabolic and behavioural roles in normal function with how dysfunction may contribute to the development of AN.